The Sa'dan Toradja chant for the deceased - Veen, H. van der (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1966)
The book discusses the cult of the dead within the religion of the Sa'dan Toradja, practiced among the main group of people inhabiting the South Toradja area, South Celebes, Indonesia. The death ritual, the aluk to mate, consists of many ceremonies, one of which is the singing of a chant for the deceased called the badon during a feast. The book provides examples of variations, circumstances of the performance, and interpretations of meaning for the chant.